Ceramic slurry, ceramic substrate and preparation method thereof

By optimizing the composition distribution ratio of ceramic slurry, using aluminum nitride, zirconium oxide and beryllium oxide as thermal conductors, and adding TiN, ZrO2 and CaC2 as sintering additives, it is solved that it is difficult for ceramic substrates to achieve high strength and high thermal conductivity at the same time. The problem of this paper achieves high thermal conductivity, high strength and good insulation performance of the ceramic substrate.

CN119430877APending Publication Date: 2025-02-14NANCHONG THREE CIRCLE ELECTRONICS +1

Patent Information

Application Number
CN202411490876.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

It is difficult for existing ceramic substrates to achieve high strength and high thermal conductivity at the same time, resulting in insufficient performance when used in electronic components.

Method used

By optimizing the component distribution ratio of the ceramic slurry, including the use of aluminum nitride, zirconium oxide and beryllium oxide as thermal conductors, and the addition of TiN, ZrO2 and CaC2 as sintering aids, it is necessary to improve the thermal conductivity and strength of the ceramic substrate.

Benefits of technology

It achieves high thermal conductivity, high strength and good insulation performance of ceramic substrates, meeting the demand for high-performance ceramic substrates of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430877A_ABST
    Figure CN119430877A_ABST
Patent Text Reader

Abstract

The invention relates to ceramic slurry, a ceramic substrate and a preparation method thereof, and belongs to the technical field of ceramic materials. The ceramic slurry provided by the invention comprises the following components in parts by weight: 85-90 parts of aluminum oxide powder, 6-15 parts of heat-conducting powder, 1-7 parts of a plasticizer, 3-9 parts of a sintering aid, 2-6 parts of a dispersing agent, 2-5 parts of a viscosity modifier and 10-15 parts of a solvent, the heat-conducting powder comprises aluminum nitride, zirconium oxide and beryllium oxide; the sintering aid is prepared from TiN, ZrO2 and CaC2. According to the invention, the heat-conducting powder and the sintering aid are added into the ceramic slurry, and are reasonably proportioned with other components, so that the high-heat-conductivity and high-strength ceramic substrate is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a ceramic slurry, a ceramic substrate and a preparation method thereof. Background Art

[0002] In recent years, due to the rapid development of electronic technology, electronic components are moving towards miniaturization, lightweight, integration, high reliability and high power output. The performance requirements for ceramic substrates, one of the main components that play the role of bearing components, external connection, protection and cooling, are becoming increasingly higher, mainly reflected in the requirements for its thermal conductivity, strength, dielectric properties, heat dissipation and insulation properties.

[0003] In the process of theoretical research and industrialization, ceramic substrates are mainly composed of alumina as the main component, and a certain amount of zirconium oxide, yttrium oxide and other additives are added. After high-temperature sintering, a substrate with a bending strength of 450MPa is obtained. However, it is difficult for the substrate to achieve high strength and high thermal conductivity at the same time. This is because when a high-strength substrate is to obtain a high thermal conductivity, the alumina crystal particles need to grow to a certain extent to reduce the grain boundary glass layer, thereby reducing the thermal conductivity barrier. However, when the alumina crystal particles grow, abnormal grain growth is prone to occur, and the enlargement of the grains will also lead to a decrease in the strength of the substrate.

[0004] Therefore, it is urgent to develop ceramic substrates with both high strength and high thermal conductivity to meet the needs of the rapid development of the electronic and electrical industry. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a ceramic slurry, a ceramic substrate and a preparation method thereof.

[0006] The present invention is achieved through the following technical solutions:

[0007] In the first aspect, the present invention provides a ceramic slurry, comprising the following components, by weight: 85-90 parts of alumina powder, 6-15 parts of thermal conductive powder, 1-7 parts of plasticizer, 3-9 parts of sintering aid, 2-6 parts of dispersant, 2-5 parts of viscosity regulator, and 10-15 parts of solvent; the thermal conductive powder comprises aluminum nitride, zirconium oxide and beryllium oxide; the sintering aid comprises TiN, ZrO2 and CaC2.

[0008] According to quantum theory, the energy of lattice vibration is quantized, called phonon. The heat conduction of inorganic non-metallic materials is realized by the vibration of crystal lattice. The vibration kinetic energy of particles on the lattice in the high-temperature part of the crystal is large, while in the low-temperature part, the vibration kinetic energy of particles is small. The vibration of particles will affect each other, and the part with large kinetic energy will be transferred to the part with small kinetic energy, thereby realizing the conduction of heat. The heat conduction of solid medium can be regarded as the transmission of continuous non-resonant elastic waves through phonons or the quantum of interaction between heat energy and phonons. Oxygen impurities in the lattice will cause scattering of lattice waves, thereby reducing the mean free path of phonons. The smaller the mean free path, the lower the thermal conductivity. The present invention uses aluminum nitride, zirconium oxide and beryllium oxide as thermal conductive powder. During the sintering process, the thermal conductive powder can make up for the lattice defects between aluminum oxide crystals, increase the heat conduction path or increase the mean free path of phonons, and improve the thermal conductivity of the substrate. Above 1300°C, alumina is in the α-Al2O3 crystal form. The higher the temperature, the larger the crystal grows, which affects the strength of the substrate. Furthermore, the present invention uses TiN, ZrO2 and CaC2 as sintering aids, which can combine with alumina, which is beneficial to the removal of oxygen impurities and purification of the crystal lattice. The added sintering agent can quickly form a low-temperature liquid phase, and the generated liquid phase has wettability to the alumina particles, which is beneficial to the growth of alumina grains. At the same time, if the amount of thermally conductive powder added is too much, the strength of the substrate will be reduced; if the amount added is too little, the alumina lattice will have defects and the thermal conductivity cannot be improved. The present invention optimizes the amount of thermally conductive powder and sintering aid added, and reasonably compounded with the other components to obtain an alumina ceramic substrate with strength, thermal conductivity and insulation properties.

[0009] Preferably, in the thermally conductive powder, the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:(0.3-1):(0.3-1).

[0010] More preferably, in the thermally conductive powder, the weight ratio of the aluminum nitride, zirconium oxide, and beryllium oxide is 1:(0.5-0.7):(0.5-0.7).

[0011] In the thermally conductive powder of the present invention, aluminum nitride can form a eutectic with aluminum oxide, and a large amount of zirconium oxide and beryllium oxide added affects the growth of aluminum oxide crystals and destroys the integrity of the crystal phase. When the three meet the above ratio, the ceramic substrate can have better performance.

[0012] Preferably, in the sintering aid, the weight ratio of TiN, ZrO2 and CaC2 is (1-8): (1-7): 1.

[0013] More preferably, in the sintering aid, the weight ratio of TiN, ZrO2 and CaC2 is (5-7):(2-4):1.

[0014] Preferably, the average particle size of the alumina powder is (D50): 3 μm-5 μm.

[0015] Preferably, the average particle size of the thermally conductive powder is (D50): 0.3 μm-3 μm.

[0016] More preferably, the average particle size of the thermally conductive powder is (D50): 0.3 μm-1.2 μm.

[0017] Preferably, the plasticizer includes at least one of dibutyl phthalate (DBP), polyethylene glycol, glycerol, and dioctyl phthalate (DOP).

[0018] Preferably, the dispersant includes at least one of triolein, polyethylene glycol, citric acid, and tetramethyldisilazane.

[0019] Preferably, the viscosity modifier includes at least one of polyvinyl butyral (PVB), ethyl cellulose, polymethyl acrylate, and ethylene-methyl acrylate copolymer; further, the viscosity modifier includes polyvinyl butyral (PVB).

[0020] Using PVB as a viscosity regulator can meet the mechanical and thermal properties of the green porcelain molding process. The molded product has good stability and a stable shrinkage rate after sintering.

[0021] Preferably, the solvent includes at least one of butanol, isopropanol, ethanol, toluene and xylene; further, the solvent includes butanol and isopropanol.

[0022] The present invention can use butanol and isopropanol as the solvent system, which can effectively reduce the pollution to human body and environment in the production process, and is conducive to energy saving, emission reduction and cost reduction.

[0023] In a second aspect, the present invention provides a method for preparing the ceramic slurry, comprising the following steps:

[0024] The alumina powder, thermal conductive powder, solvent, dispersant and sintering aid are mixed according to the weight proportions, ball-milled, and then a plasticizer and a viscosity regulator are added and ball-milled continuously to obtain the ceramic slurry.

[0025] Preferably, the ball milling time is 4h-36h, and the ball milling speed is 280-320r / min; the continued ball milling time is 12h-48h, and the ball milling speed is 60-80r / min.

[0026] In a third aspect, the present invention provides a method for preparing a ceramic substrate, comprising the following steps: degassing, casting, stamping, debinding, and sintering the ceramic slurry to obtain the ceramic substrate.

[0027] In the preparation method of the present invention, the green porcelain slurry is first subjected to a degassing treatment under a low vacuum condition; then, the treated green porcelain slurry is made into a tape-cast green body with a specific thickness and width by a tape-casting machine; then, the tape-cast green body is stamped and formed, and then the formed green body is sent to a debinding kiln for debinding treatment, and then transferred to a sintering kiln for sintering. The preparation method of the ceramic substrate of the present invention is easy to operate, simple in process, and can be applied to industrial large-scale production.

[0028] Preferably, the debinding temperature is 100°C-350°C, and the debinding time is 5h-8h; the sintering temperature is 1450°C-1550°C, and the sintering time is 13h-15h.

[0029] In a fourth aspect, the present invention provides a ceramic substrate prepared by the ceramic substrate preparation method.

[0030] The present invention has the following beneficial effects:

[0031] The present invention optimizes the ratio of alumina powder and other components to reduce the content of oxygen impurities in the lattice, thereby improving thermal conductivity. At the same time, the addition of the sintering aid of the present invention can combine with alumina, can reduce the sintering temperature, and is conducive to the effective removal of oxygen impurities. The low-temperature sintering agent does not react with aluminum nitride, and will not produce lattice defects, which is conducive to the formation of a complete crystal form of polyhedral aluminum nitride; the thermal conductivity of aluminum nitride is 170-320w / mk, and adding it to alumina can effectively improve the thermal conductivity. The present invention obtains a ceramic substrate with high thermal conductivity and high strength by adding thermal conductive powder and sintering aid to the ceramic substrate material and reasonably matching it with the other components. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of volume resistivity sample preparation in performance testing;

[0033] Figure 2 Schematic diagram of breakdown strength sample preparation in performance testing. DETAILED DESCRIPTION

[0034] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0036] Embodiment 1-35

[0037] The compositions of the ceramic slurries of Examples 1-35 of the present invention are shown in Table 1.

[0038] The method for preparing the ceramic slurry of Example 1-35 comprises the following steps:

[0039] Alumina powder, thermal conductive powder, solvent, dispersant and sintering aid were mixed according to the weight proportions as described in Table 1, zirconium dioxide balls were added and ball milled for 20 hours at room temperature, with a ball mill speed of 300 r / min, and then plasticizers and viscosity regulators were gradually added, and ball milling was continued for 30 hours at room temperature, with a ball mill speed of 80 r / min to obtain ceramic slurry.

[0040] Comparative Examples 1-7

[0041] The difference between each comparative example and the embodiment is only in the type and content of the components, as shown in Table 1.

[0042] Among the components described in the embodiments and comparative examples,

[0043] The thermal conductive powder D1 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of the aluminum nitride, zirconium oxide and beryllium oxide is 1:0.5:0.6;

[0044] The thermal conductive powder D2 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:0.6:0.7;

[0045] The thermal conductive powder D3 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:0.7:0.5;

[0046] The thermal conductive powder D4 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of the aluminum nitride, zirconium oxide and beryllium oxide is 1:0.7:0.7;

[0047] The thermal conductive powder D5 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of the aluminum nitride, zirconium oxide and beryllium oxide is 1:0.5:0.5;

[0048] The thermal conductive powder D6 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of the aluminum nitride, zirconium oxide and beryllium oxide is 1:0.6:0.6;

[0049] The thermal conductive powder D7 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:0.3; 0.7;

[0050] The thermal conductive powder D8 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:1; 0.6;

[0051] The thermal conductive powder D9 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:0.7; 1;

[0052] The thermal conductive powder D10 is aluminum nitride, zirconium oxide and beryllium oxide; the weight ratio of the aluminum nitride, zirconium oxide and beryllium oxide is 1:0.7:0.3;

[0053] The thermal conductive powder D11 is aluminum nitride and zirconium oxide; the weight ratio of aluminum nitride to zirconium oxide is 1:0.6;

[0054] The sintering aid Z1 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 5:2:1;

[0055] The sintering aid Z2 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 7:4:1;

[0056] The sintering aid Z3 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 6:4:1;

[0057] The sintering aid Z4 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 7:3:1;

[0058] The sintering aid Z5 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 4:7:1;

[0059] The sintering aid Z6 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 5:1:1;

[0060] The sintering aid Z7 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 1:2:1;

[0061] The sintering aid Z8 is TiN, ZrO2, and CaC2, and the weight ratio of TiN, ZrO2, and CaC2 is 8:3:1;

[0062] The average particle size of the alumina powder is (D50) 5 μm;

[0063] The average particle size of the thermally conductive powders of Examples 1-23, 27-34, and Comparative Examples 1-7 is (D50) 0.5 μm; the average particle size of the thermally conductive powder of Example 24 is (D50) 0.3 μm; the average particle size of the thermally conductive powder of Example 25 is (D50) 1.2 μm; the average particle size of the thermally conductive powder of Example 26 is (D50) 0.8 μm; the average particle size of the thermally conductive powder of Example 35 is (D50) 3 μm;

[0064] The plasticizer is DBP;

[0065] The dispersant is triolein;

[0066] The viscosity modifier is PVB;

[0067] The solvent is butanol and isopropanol in a weight ratio of 1:1.

[0068] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0069] Table 1 Content of each component in the ceramic slurry of the embodiment and the comparative example

[0070]

[0071]

[0072]

[0073] The ceramic slurries of the embodiments and comparative examples are made into ceramic substrates for testing the ceramic forming performance. The preparation method of the ceramic substrate comprises the following steps:

[0074] The ceramic slurry obtained in the embodiment and the comparative example is subjected to low vacuum to remove bubbles, and then the raw ceramic slurry is made into a strip-shaped sheet material of a certain thickness and width using a tape casting machine to obtain a tape-cast green body, which is then stamped and formed using a molding machine to obtain a molded green body, which is then sent to a debinding kiln at a temperature of 200°C for debinding for 5 hours. The debinding product is sent to a sintering kiln and sintered at 1500°C for 15 hours to obtain the ceramic substrate.

[0075] The ceramic substrates of the embodiments and comparative examples were tested for performance, and the testing method was as follows:

[0076] 1. Mechanical properties:

[0077] 1.1 Fracture toughness: The fracture toughness of the material is measured by the single-edge notched beam method (SENB method) using a WDW electronic universal testing machine, with the loading rate set to 0.05 mm / min. The calculation formula is:

[0078]

[0079] In the formula: Y=1.93-3.07(a / w)+13.66(a / w) 2 -23.98(a / w) 3 +25.22(a / w) 4 ;

[0080] K IC —Expressed as fracture toughness, MPa·m 1 / 2 ;

[0081] P—represents the load when the sample breaks, N;

[0082] L—expressed as the span between supports, mm;

[0083] a—indicates the depth of the sample cut, mm;

[0084] b—expressed as the width of the specimen section, mm;

[0085] w—represents the sample cross-sectional height, mm.

[0086] 1.2 Strength: The substrate is scribed by laser to the size of l×b×h=36mm×3mm×4mm, and the strength of the substrate is tested by a strength tester;

[0087] 2. Thermal performance

[0088] 2.1 Thermal conductivity: The material is laser scribed into Φ10 mm discs with a thickness of less than 1 cm, and the thermal conductivity is tested using a thermal conductivity meter.

[0089] 2.2 Thermal shock resistance: Place the indentation side upward on a 180℃ platen, keep warm for 30 seconds, then put it into a 25℃ water tank, dry it in a 100℃ oven, paint it red, and count the number of cracks. Test 100 samples in each group and count the crack rate;

[0090] 3. Electrical properties:

[0091] 3.1 Volume resistivity:

[0092] ①Sample preparation:

[0093] a. Laser scribing: Sample size: Disk Figure 1 As shown, at least 5 pieces are tested for each group of samples.

[0094] b. Silver plating should be done according to the drawing. The silver electrode should be complete. Figure 1 As shown, the upper surface is a ring: outside Lower surface:

[0095] ②Test: Test according to the method specified in GB 5594.5: Qualified standard ≥1×10 14 Ω·cm.

[0096] 3.2 Breakdown strength:

[0097] ①Sample preparation:

[0098] a. Laser scribing: Sample size: Disk Figure 2 As shown, at least 5 pieces are tested for each group of samples.

[0099] b. Silver-plated according to the drawing, silver-plated electrodes

[0100] ②Test: Test according to the method specified in GB / T 5593:

[0101] 3.3 Dielectric constant: According to GBT5594.4-2015 "Test methods for properties of structural ceramic materials for electronic components Part 4: Determination of dielectric constant and dielectric loss tangent");

[0102] 3.4 Dielectric loss: According to GBT5594.4-2015 "Test methods for properties of structural ceramic materials for electronic components Part 4: Determination of dielectric constant and dielectric loss tangent".

[0103] The performance test results of the ceramic substrates of the embodiments and comparative examples are shown in Table 2 below.

[0104] Table 2 Performance test results of ceramic substrates of embodiments and comparative examples

[0105]

[0106]

[0107]

[0108] As can be seen from Table 2, the present invention uses aluminum nitride, zirconium oxide and beryllium oxide as thermal conductive powders, TiN, ZrO2 and CaC2 as sintering aids and reasonably compounded with other components to obtain a ceramic substrate with excellent thermal conductivity, strength and insulation performance. As can be seen from Comparative Examples 1-6, if the addition amount of a single component is too low or too high, the compatibility effect with the other components will decrease, which will further lead to a decrease in the performance of the ceramic substrate. In Comparative Example 7, the thermal conductive powder does not contain beryllium oxide, and the overall performance of the ceramic substrate decreases, indicating that the present invention uses aluminum nitride, zirconium oxide and beryllium oxide as thermal conductive powders, and optimizes the ratio between the components of the ceramic substrate to enable the ceramic substrate to have high thermal conductivity, high strength and good insulation performance.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A ceramic slurry, characterized in that: The invention comprises the following components by weight: 85-90 parts of alumina powder, 6-15 parts of thermal conductive powder, 1-7 parts of plasticizer, 3-9 parts of sintering aid, 2-6 parts of dispersant, 2-5 parts of viscosity regulator and 10-15 parts of solvent; the thermal conductive powder comprises aluminum nitride, zirconium oxide and beryllium oxide; the sintering aid comprises TiN, ZrO2 and CaC2.

2. The ceramic slurry according to claim 1, characterized in that In the thermally conductive powder, the weight ratio of aluminum nitride, zirconium oxide, and beryllium oxide is 1:(0.3-1):(0.3-1).

3. The ceramic slurry according to claim 2, characterized in that: In the thermally conductive powder, the weight ratio of aluminum nitride, zirconium oxide and beryllium oxide is 1:(0.5-0.7):(0.5-0.7).

4. The ceramic slurry according to claim 1, characterized in that In the sintering aid, the weight ratio of TiN, ZrO2 and CaC2 is (1-8): (1-7):

1.

5. The ceramic slurry according to claim 1, characterized in that: The average particle size of the thermally conductive powder is 0.3 μm-3 μm.

6. The ceramic slurry according to claim 1, characterized in that The average particle size of the alumina powder is 3 μm-5 μm.

7. The ceramic slurry according to claim 1, characterized in that The plasticizer includes at least one of dibutyl phthalate, polyethylene glycol, glycerol, and dioctyl phthalate; and / or the dispersant includes at least one of triolein, polyethylene glycol, citric acid, and tetramethyldisilazane; and / or the viscosity modifier includes at least one of polyvinyl butyral, ethyl cellulose, polymethyl acrylate, and ethylene-methyl acrylate copolymer; and / or the solvent includes at least one of butanol, isopropanol, ethanol, toluene, and xylene.

8. The method for preparing the ceramic slurry according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing alumina powder, thermal conductive powder, solvent, dispersant and sintering aid according to the weight proportions, ball milling, adding plasticizer and viscosity regulator, and continuing ball milling to obtain the ceramic slurry.

9. A method for preparing a ceramic substrate, characterized in that: The method comprises the following steps: degassing, casting, stamping, debinding and sintering the ceramic slurry according to any one of claims 1 to 7 to obtain the ceramic substrate.

10. A ceramic substrate, characterized in that: It is prepared by the preparation method described in claim 9.

Citation Information

Patent Citations

  • Sintered alumina-zirconia substrate for a semiconductor device and process for its preparation

    CN102850043A

  • Alumina ceramic and preparation method thereof

    CN109836135A

  • Alumina Composite Ceramic Composition and Method of Manufacturing the Same

    US20170152424A1

Cited By

  • High-thermal-conductivity aluminum oxide ceramic and preparation process thereof

    CN119462104A

  • High thermal conductivity aluminum oxide ceramic and preparation process thereof

    CN119462104B